PENGARUH INFLASI, NON PERFORMING FINACING (NPF) DAN BI RATE TERHADAP PEMBIAYAAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) PADA BANK UMUM SYARIAH 2012-2017 (STAI BHAKTI PERSADA BANDUNG, 2018)
This study aimed to analyze the effects of inflation, Non Performing Financing and BI rate on Micro Small and Medium Enterprises (SME) of Islamic Banks in Indonesia 2012-2017. The population in this research are all Islamic Banks in Indonesia 2012-2017. The research method that is used in this study is explanatory research method. The method of data analysis that is used in this research is multiple linear regression analysis. The results of this study indicate that inflation  growth partially is unable to explain the variable SME; NPF partially able to explain the variable of SME and BI Rate partially able to explan no significantly  the variable of SME. Simultaneously inflation, NPF and BI Rate influenced SME of Islamic Banks in Indonesia period 2012-2017.